Impact of cochlear implantation on quality of life and mental comorbidity in patients aged 80 years. (14th April 2016) - Knopke, Steffen; Gräbel, Stefan; Förster‐Ruhrmann, Ulrike; Mazurek, Birgit; Szczepek, Agnieszka J.; Olze, Heidi
Abstract : Objectives/Hypothesis: The objective of this study was to evaluate the outcome of cochlear implantation in elderly patients (80 or older) with progressive bilateral deafening. The measured outcomes included the quality of life, speech understanding, tinnitus distress, stress level, anxiety, and depressiveness. Study Design: Prospective cohort study. Methods: Seventeen 80+ years (mean 82.9 ± 2.7 years) patients with progressive, postlingual, bilateral deafness were unilaterally implanted with multichannel cochlear implants. Data about their health‐related quality of life (Nijmegen Cochlear Implantation Questionnaire) and their comorbidities were collected using specific validated questionnaires (tinnitus questionnaire, General Anxiety Disorder‐7, Depression Scale, Perceived Stress Questionnaire). The speech understanding was assessed with the Freiburg Monosyllabic Test, whereas the subjective hearing was evaluated with the Oldenburg Inventory. Results: After the surgery, not only the subjective hearing but also health‐related quality of life, speech understanding, and tinnitus distress of the implanted patients improved significantly. The perceived stress, general anxiety, and depressiveness were low or normal prior and after surgery. Conclusion: This study demonstrates a significant improvement in the quality of life and speech understanding in a group of elderly patients who underwent cochlear implantation. An additional positive indicator of a promising hearing rehabilitation was a significant improvement of the tinnitus distress. Perceived stress level, general anxiety, and the depressiveness of implanted patients were low and remained unaffected. Level of Evidence: 4. Laryngoscope, 126:2811–2816, 2016